1994
DOI: 10.1152/ajpgi.1994.267.4.g595
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cholecystokinin secretion by ATP-sensitive potassium channels

Abstract: The relationship of potassium channel activity to the secretion of cholecystokinin (CCK) was evaluated in STC-1 cells, an intestinal CCK-secreting cell line. Patch-clamp and 86Rb efflux studies showed that an ATP-sensitive potassium channel was endogenously expressed in STC-1 cells. Furthermore, channels are present in sufficient number to significantly modulate whole cell potassium permeability after either channel activation or closure with diazoxide (100 microM) or disopyramide (200 microM), respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Patch-clamp studies have also demonstrated the presence of K ATP channels in parent STC-1 cells (2,28,30,58). Thus it has been proposed that they play a role in regulating CCK secretion (2,27,28). However, the results presented in this paper suggest that K ATP channels play, at best, a very minor role in regulating CCK secretion, since CCK-producing cells in vivo do not express detectable levels of Kir 6.1 or Kir 6.2.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Patch-clamp studies have also demonstrated the presence of K ATP channels in parent STC-1 cells (2,28,30,58). Thus it has been proposed that they play a role in regulating CCK secretion (2,27,28). However, the results presented in this paper suggest that K ATP channels play, at best, a very minor role in regulating CCK secretion, since CCK-producing cells in vivo do not express detectable levels of Kir 6.1 or Kir 6.2.…”
Section: Discussionmentioning
confidence: 65%
“…This conclusion is consistent with our in vivo immunohistochemical studies indicating that gut L cells, like gut K cells, do not express detectable Kir 6.1 or Kir 6.2. Patch-clamp studies have also demonstrated the presence of K ATP channels in parent STC-1 cells (2,28,30,58). Thus it has been proposed that they play a role in regulating CCK secretion (2,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of Kir6.2 and SUR1 by RT-PCR is consistent with the electrophysiological finding that the channels were sensitive to tolbutamide and diazoxide. K ATP channels have been detected previously in the poorly differentiated and multipotential CCK-secreting cell line STC-1, which also releases GIP and GLP-1 (31)(32)(33). CCK secretion from STC-1 cells was stimulated by 5 and 25 mmol/l glucose and by the nonspecific channel blocker disopyramide (31).…”
Section: Discussionmentioning
confidence: 80%
“…ATP-sensitive K ϩ channels regulating basal membrane potential (20,23) can be affected by CaSR. However, there was no difference in basal secretion between CaSR WT and KO CCK-eGFP cells.…”
Section: Discussionmentioning
confidence: 99%